Modeling and simulation of the current quenching behavior of a line lightning protection device. (9th February 2017) - Mürmann, Mario; Chusov, Alexander; Fuchs, Roman; Nefedov, Alexander; Nordborg, Henrik
Abstract: We develop a consistent model for a line lightning protection device (LLPD) and demonstrate that it can explain the two modes of current quenching—impulse quenching and current zero quenching—observed in such devices. A dimensional analysis shows that impulse quenching can always be obtained if the power loss from the electric arcs is large enough as compared to U 0 I f, where U 0 is the grid voltage and I f is the maximum follow current after a lightning strike. We further show that the two modes of quenching can be reproduced in a full 3D arc simulation coupled to the appropriate circuit model, which allows us to analyze the power loss from the arc in greater detail. Because of the high temperature, the main mechanism of power loss is radiation which has to be correctly modeled in order to obtain physically meaningful results. The results will allow us to use numerical simulations to optimize the quenching ability to LLPDs in the future.